1984
DOI: 10.1152/ajprenal.1984.246.6.f937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcium and sodium transport in early and late rat distal tubules: effect of amiloride

Abstract: In vivo tubular microperfusion experiments were performed in rats to compare the function of the early and late rat distal convoluted tubule and to examine the effect of amiloride on distal Na and Ca reabsorption. In clearance experiments, amiloride (6 micrograms/min) reduced fractional Ca excretion (P less than 0.05) and the calcium-to-sodium clearance ratio (P less than 0.001) without affecting fractional Na excretion. The in vivo microperfusion experiments revealed a higher rate of osmotic water flow in lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 0 publications
8
45
0
Order By: Relevance
“…On the contrary, the slightly stimu latory effect of benzamil on basal Ca2* transport suggests that Na* entry rather exerts a negative feedback on Ca2* transport. Similar stimulatory effects of amiloride ana logues on active Ca2* reabsorption have been reported in literature [12]. One explanation for this finding might be that the activity of the basolateral Na*-Ca2* exchanger, which plays an important role in transepithclial Ca2* transport [4], is already inhibited at basal intracellular Na* levels.…”
Section: Discussionsupporting
confidence: 86%
“…On the contrary, the slightly stimu latory effect of benzamil on basal Ca2* transport suggests that Na* entry rather exerts a negative feedback on Ca2* transport. Similar stimulatory effects of amiloride ana logues on active Ca2* reabsorption have been reported in literature [12]. One explanation for this finding might be that the activity of the basolateral Na*-Ca2* exchanger, which plays an important role in transepithclial Ca2* transport [4], is already inhibited at basal intracellular Na* levels.…”
Section: Discussionsupporting
confidence: 86%
“…In general, amiloride-sensitive currents decreased in the following order: CNT Ͼ initial CD Ͼ CD (13). These findings on apical ENaC localization and activity are consistent with previous studies on microperfused rat tubules (14,15) and on isolated rabbit tubules (16) that established several times higher sodium transport rates in early ASDN (DCT and CNT) than in ASDN segments farther downstream (CD), and also with studies that showed a progressive decrease of the basolateral Na-K-ATPase activity along the ASDN (17). Taken together, the data clearly suggest that the aldosterone-dependent adaptation of renal sodium excretion to dietary sodium intake occurs predominately in the early ASDN, whereas the late ASDN gets recruited only under high plasma aldosterone levels.…”
Section: Enac and The Aldosterone-sensitive Distal Nephronsupporting
confidence: 92%
“…It is most pronounced in the early ASDN portions (late DCT and early CNT) and progressively decreases along further downstream localized segments (late CNT and CD) (2,6). This morphologically ascertainable gradient is consistent with numerous functional studies showing several-fold higher transepithelial Na ϩ transport rates and ENaC activity in the CNT than in the CD (7)(8)(9)(10)(11). However, the underlying molecular mechanisms for this axial heterogeneity are unclear.…”
supporting
confidence: 86%
“…Whereas Nedd4-2 immunostaining increased along the axis of the ASDN, apical ENaC localization decreased. The axial gradient of apical ENaC localization was seen in several species and was evident also in microperfusion, micropuncture, and patch-clamp studies that showed much higher ENaC activity in early ASDN (i.e., the CNT) than in late ASDN segments (i.e., the CD) (2,(7)(8)(9)(10)(11)29). Differences in the expression levels of mineralocorticoid receptor 11-␤HSD2 and SGK1 likely do not account for this axial heterogeneity, because these ENaC-regulating molecules seem to be equally abundant along the CNT and CCD (reviewed in [(47]).…”
Section: Discussionmentioning
confidence: 76%